Philosophical investigation of Al-Zarnuji's Ta'lim Al-Muta'allim: strengthening ethical engagement into teaching and learning - Huda, Miftachul (Medwell Journals, 2016)
There emerge the issues on how the process of teaching and learning should be implemented in the way that ethical consideration becomes entirely a main concern to enhance the personality with admirable attitude. There has been lack of scholarly attention to elaborate the philosophical inquiry into the foundational stage especially referring to Muslim scholarly work. This research aims to investigate the philosophical inquiry of Al-Zarnuji’s ideas in his concept of Ta’lim al-Muta’allim. This work serves as a source of guidance for Islamic education because it presents fascinating theories on teaching and learning. Literature review was conducted to examine the conceptual framework to the contemporary perspective. The findings reveal ethical engagement which al-Zarnuji concerns refers to strengthening the process of learning and teaching. This becomes central to drive the process itself into the enhancement to the target supposed in the way that there is no separated form in the process of transfer both knowledge and value.